Եդեսիայի Աբգար թագավորի վարքաբանական զրույցը և նրա կերպափոխությունները հայ մատենագրության մեջ - Ազատյան, Շավարշ
The hagiographic legend of King Abgar of Edessa had a long period of development in Old Armenian literature. It is attested in works of various genres and has undergone changes according to their requirements. Movses Khorenats‘i was the only historiographer of the Golden Age who re-narrated the legend of Abgar and in fact created its Armenian version, which has certain differences from the original Syrian legend. Khorenats‘i’s Abgar and his princes are Armenians, and Edessa-Osroene is an Armenian kingdom. The historiographer’s goal was to Armenize the first Christian king and to enhance the pres-tige of the Armenian Church. Агиографическая легенда об эдесском царе Абгаре прошла долгий путь развития в древнеармянской литературе. Она засвидетельствована в произведениях различных жанров, при этом претерпела соответствующие изменения. Из историков Золотого века, Мовсес Хоренаци пересказал легенду об Абгаре и фактически создал ее армянскую версию, в некоторых деталях отличную от сирийской легенды. У Хоренаци Абгар и его нахарары (князья) армяне, а Эдесса-Осроена – армянское царство. Целью Хоренаци была арме-низация первого христианского царя и придание большего авторитета армян-ской церкви
Keywords: Պատմագրություն; Բանահյուսություն